Modelling the HYPHI digester process for methanization of pig manure - Ngo Van Thanh; Tentscher, Wolfgang; Surapong Chiraratananon; Edelman, David J.; The Government of French (Bangkok : Asian Institute of Technology, 1991)
A kinetic model for digestion of pig manure with high concentration of suspended matter was developed based on HASHIMOTO's model. At first, this model was verified with 32 actual data points. Furthermore, a term for the death rate of microbial organisms was introduced. It was applied for computing the optimum conditions for volumetric loading rate rv,CH4 (m3 CHJm3 r.d) at a given temperature. The hydraulic retention time eH was varied from 2 to 25 days with increments of 1 day and the influent VS concentration Cvso (kgVSjm3 r) was varied from 1 to 100 with increments of 0.1. It was shown that, under tropical climate with average temperatures of 30°C, maximum values of rv,CH4 occur at eH ""' 10 days and Cvso ""' 70 (kgVSjm3 }, therefore, the volume of the digester may be reduced and total investment costs can be decreased. The average ultimate methane yield B0 is about 0.5 (m3 CHJkgVS0 ). Computation on the effects of Cvso on the kinetic parameter K was determined by eq. 5.2.1. Fig. 5.2.1 showed that threshold concentration of influent VS concentration can be up to over 80 (kgVSjm3 r) without causing inhibition. Thereby, confirming experimental results of HILL D.T. and co workers (1986). The exact solution of the first order differential equation was used for kinetic description of the low solids reactor. In this case, the kinetic parameter K1 (day)"1 does not only depend on temperature, but also on type of the material and configuration of the packed bed. The HYPHI computer package was written for biogas plant systems with four modifications (Plug-Flow Reactor Only, Plug-Flow with Settler, HYPHI system with a PF Reactor and AF Reactor and HYPHI system with PF Reactor and UASB Reactor) to design and model all biogas systems. The program environment of Turbo-Pascal Version 6.0 was used for the HYPHI package.
A Thesis submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science, School of Environmental, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: HYPHI (Computer program); Farm manure; Biogas